What are Wits female students' perceptions of the impact of hegemonic masculinity on their decision-making for birth control? - Joyi, Naledi (My University, 2021)
This paper explores the Wits female students’ perceptions of the impact of hegemonic masculinity on their decision making for birth control. The paper explores power dynamics within heterosexual relationships, and how this impact the process of decision- making pertaining to contraceptive use. Women are represented as victims of their environment when it comes to sexual health and contraceptive use, this takes away the agency of women. This paper is aware that when there is oppression, there is also resistance therefore women are not absolutely oppressed. The social practices of heterosexuality and other institutions contribute to the maintenance of hegemonic masculinity. This study’s aim is to understand how women navigate heterosexual matrix and how it contributes to their decision-making process. Research on factors that contribute to decision making are often focused on couples, and married people negating adolescents. South Africa’s high HIV rates suggests that adolescents are some of the most affected. Therefore, interrogating power dynamics in adolescents will assist contribute to conversations and knowledge around multiple factors that contribute to decision making process for young women. Semi-structured interviews were used to capture the perceptions and experiences of young women from the University of Witwatersrand, and how they navigate the spaces that relate to sexual and reproductive health. Findings highlight gender inequity within heterosexual relationships, and bodily integrity. They also highlight the barriers that are related to sexual activity among adolescent women, how the stigma leads to the lack of information, and discrimination against adolescents in public health clinics and hospitals. The culture of the public health system is compared to private health system. Findings also showed factors that contribute to adolescent understanding and navigation of self within relationships relates to growth physical, emotionally, and experientially. The data set presented an emphasis of advantages triumphing over disadvantages of contraceptive. A shift in narrative was highlighted which suggests that women challenge the heteronormative ideals within society and women’s agency is emphasized in their talk about sexual experience and navigating heterosexual relationships at large
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts by Coursework and Research Report to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021